A Study of Microbiological Contamination in Cosmetics and Toiletries in Iraq. Contamination of Talcum Powder and Body Lotion - Raghad A. Razooki (College of Pharmacy / Mustansiriyah University, 2010)
One hundred items of 60 talcum powders and 40 body lotions were examined for their total aerobic bacterial, coliform and fungal counts. We also carried out anaerobic bacterial counts for talcum powder as well as tests to detect some potentially hazardous bacteria in all tested samples. Talcum powders were more heavily contaminated with bacteria than body lotions. More than 60% of the tested body lotions contained no viable bacteria or less than 100 C.F.U./gm, while 35% of the talcum powders contained this level. Five per percent of the talcum powder were contaminated with 104 C.F.U. /gm and none of the body lotions were contaminated to that extent. No coliforms were recovered from any of the body lotions, while 3.3% of the talcum powder examined contained coliforms in the range of 250-300 C.F.U/gm. Staphylococcus Spp. were detected in one sample of both talcum powders and body lotions. Two samples of talcum powder contained E. coli. Neither talcum powder nor body lotions showed fungal counts. Also no talcum powder showed the presence of anaerobic bacterial counts.